PL01: Creation of the Canadian Heart Failure Risk Scale for acute heart failure patients. (15th May 2017) - Stiell, I.G.; Clement, C.M.; Perry, J.J.; Brison, R.J.; McRae, A.; Rowe, B.H.; Borgundvaag, B.; Aaron, S.; Mielneczuk, L.; Calder, L.; Brinkhurst, J.; Forster, A.; et al.
Abstract : Introduction: Acute heart failure (AHF) is a common, serious condition that frequently results in morbidity and death and is a leading cause for hospital admissions. There is little evidence to guide ED physician disposition decisions for AHF patients. We sought to create a risk-stratification tool for use by ED physicians to determine which AHF patients are at high risk for poor outcomes.Methods: We conducted a prospective cohort study in 9 tertiary hospital EDs and enrolled adult patients presenting with shortness of breath due to AHF. Patients were assessed for standardized clinical and laboratory variables and then followed to determine short-term serious outcome (SSO), defined as death, intubation, myocardial infarction, or relapse requiring admission within 14 days. We identified predictors of SSO by stepwise logistic regression and then rounded beta coefficients to create a risk scale.Results: We enrolled 1, 733 patients with mean age 77.1 years, male 54.5%, and initially admitted 50.1%. SSOs occurred in 202 (11.7%) cases (14.0% in those admitted and 9.3% in those discharged from the ED). We created the CHFRS consisting of:1. Initial Assessment a) History of valvular heart disease b) On anti-arrhythmic c) Arrival heart rate ≥ 110d) Treated with non-invasive ventilation2. Investigations a) Urea >12 mmol/L or Cr>150 µmol/L b) Serum CO2>35 mmol/L or pCO2 >60 mmHg (VBG or ABG) c) Troponin >5x Upper Reference Level 3. Fails reassessment after ED treatment:(i) Resting vital signs abnormal, (SaO2 <90% on room air or usual O2, or HR >110, or RR >28); OR(ii) Unable to complete 3-minute walk test. The risk of SSO varied from 5.0% for a score of 0, to 77.4% for a score of 9. Discrimination between SSO and no SSO cases was good with an area under the ROC curve of 0.70 (95% CI 0.66-0.74). There was good calibration between the observed and expected probability of SSO and internal validation showed the risk scores to be very accurate across 1, 000 replications using the bootstrap method.Conclusion: We have created the CHFRS tool which consists of 8 simple variables and which estimates the short-term risk of SSOs in AHF patients. CHFRS should help improve and standardize admission practices, diminishing both unnecessary admissions for low-risk patients and unsafe discharge decisions for high-risk patients. This will ultimately lead to better safety for patients and more efficient use of hospital resources.